Determining factors in the vaccination coverage of the basic immunization scheme in childhood (Research, Society and Development, 2023)
This study aims to describe the determining factors in childhood immunization with the basic scheme present in the literature. This is a bibliographical research, of the integrative literature review type, developed in the databases of the Virtual Health Library (BVS), between January and July 2023, using Health Science Descriptors (DeCS): “Cobertura vacinal”, “imunização”, “lactentes” and “crianças”, in addition to their English counterparts. A total of 185 studies were found, of which 19 were included in the sample. Barriers to access services, whether economic, geographic or organizational, and cultural aspects can determine decision-making. Common factors in the pre- and post-pandemic period were found, namely: socioeconomic factors linked to low income and lower educational level of the person responsible, black, living in rural areas and houses with a high number of children; logistical and managerial barriers related to the distribution and application of immunizers, structure and flows of services; in addition to difficulties in accessing vaccination services related to transportation, distance from services and opening hours. Thus, socioeconomic, logistical and managerial factors, and the pandemic, were predominant for the low vaccination coverage in the analyzed studies, requiring studies to assess their impacts on public health and the creation of validated instruments for evaluation.